Effects of melatonin treatment on germination, growth and physiological characteristics under drought stress in foxtail millet - Meng, Chaomin; Wang, Cheng; Guo, Haojie; Wang, Jinyue; Yu, Jingchen (Frontiers in Plant Science, 2025)
Melatonin is a key antioxidant that not only promotes seed germination, but also slows cellular aging and enhances stress resistance. However, the specific mechanisms underlying melatonin’s effects in foxtail millet (Setaria italica L.) are not yet fully understood. In this study, three varieties of millet - ‘Yugu 18’, ‘Jigu 38’ and ‘Changnong 35’ - served as test materials. We examined the influence of varying melatonin concentrations (0, 5, 25, 50, 75, 100, 125, 150, 200μmol·L-1) on germination, growth, photosynthetic properties, antioxidant capabilities, and osmoregulatory substance content of millet under drought conditions, using a pot experiment with PEG 6000. The results revealed that different melatonin concentrations exhibited a “low promotion and high elevation” pattern for seed germination, seedling length, and root length. At equivalent concentrations, the inhibitory effect on seed germination was strongest for ‘Yugu 18’, while it was weakest for ‘Jigu 38’ and ‘Changnong 35’. Notably, compared to no melatonin treatment, the 75μmol·L-1 melatonin treatment most significantly increased photosynthesis rate, intercellular CO2 concentration, chlorophyll content, CAT activity, and POD activity by 27.21%, 13.15%, 74.79%, 18.75% and 39.58%, respectively, while significantly reducing MDA content by 32.61%. Based on the weight calculation of principal components, the activities of POD and SOD, along with the contents of Ci, GSH, and soluble protein, were identified as the major contributors to the first five indices in the order: POD activity > Ci > GSH content > soluble protein content > SOD activity. The drought resistance of the nine treatments under drought stress was ranked: MT100 > MT75 > MT150 > MT125 > MT50 > CK > MT200 > MT25 > MT5. For the Jigu 38 cultivar, the optimal melatonin concentration was established at 75 μmol·L-1, while for Yugu 18 and Changnong 35, it was 100 μmol·L-1. This concentration effectively modulated the photosynthetic capacity, antioxidant enzyme activity, and osmotic ability of millet seedlings, thereby augmenting their drought resistance. This study offers a scientific basis for comprehending the mechanism by which melatonin mitigates drought stress in diverse millet varieties.